2007
DOI: 10.1148/rg.271065046
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Neurologic Disorders Associated with Pregnancy and the Postpartum Period

Abstract: Diverse pathologic conditions affect the central nervous system (CNS) and pituitary gland during pregnancy and the puerperium. Some are specific to the physiologic process of reproduction (eg, eclampsia, postpartum cerebral angiopathy, Sheehan syndrome, lymphocytic adenohypophysitis). Others are nonspecific but occur more often in pregnant women (eg, cerebral infarction, dural venous thrombosis, pituitary apoplexy). Recognition of the characteristic imaging findings in eclampsia, for example, may allow exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 61 publications
(67 reference statements)
2
30
0
10
Order By: Relevance
“…Furthermore, even when the imaging changes are less specific, knowledge of likely possibilities will lead to more appropriate earlier use of imaging. 14 In this study CT scan revealed normal findings in 48% of the women. In those with abnormal CT scan findings the commonest diagnosis was CVT with infarct (23%) followed by infarct (14%), PRES (6%), HLE (5%), CVT (3%), cerebral atrophy (1%).…”
supporting
confidence: 51%
“…Furthermore, even when the imaging changes are less specific, knowledge of likely possibilities will lead to more appropriate earlier use of imaging. 14 In this study CT scan revealed normal findings in 48% of the women. In those with abnormal CT scan findings the commonest diagnosis was CVT with infarct (23%) followed by infarct (14%), PRES (6%), HLE (5%), CVT (3%), cerebral atrophy (1%).…”
supporting
confidence: 51%
“…Ainda em relação ao realce, o que chamou atenção dos autores foi a ausência de distúrbios de perfusão e de sinais de infarto hepático. Como discutido, a etiopatogenia envolve dano endotelial e presença de vasoespasmo na circulação cerebral, o que já foi demonstrado através da angiografia digital, comprometendo artérias cerebrais de grosso e médio calibre, particularmente a artéria basilar 26 . Assim, acreditava-se inicialmente que poderiam ser encontradas alterações na RM relacionadas ao vasoespasmo e, conseqüentemente, redução de fluxo arterial no fígado.…”
Section: Discussionunclassified
“…An excellent review appeared in RadioGraphics (18). These latter entities are best diagnosed by MRI.…”
Section: Neurological Emergenciesmentioning
confidence: 99%